Sustainable environmental management practices and financial performance of SMEs in Ghana: the role of board effectiveness - Deodat Emilson Adenutsi; Alhassan Musah; Abigail Padi (Discover Global Society, 2025)
Abstract This study explores the impact of sustainable environmental management practices (SEMPs) on the financial performance (FP) of small and medium-sized enterprises (SMEs) in Ghana, emphasising the moderating role of board effectiveness. Data collected from 650 SMEs using structured questionnaires were analysed through structural equation modelling. Findings indicate that biodiversity management and sustainable waste management significantly enhance financial performance, with the latter having the strongest effect. However, emissions management showed no significant financial benefits, highlighting limited returns on emissions-focused investments among Ghanaian SMEs. Board effectiveness significantly amplified the positive impacts of biodiversity and waste management on financial outcomes, demonstrating the importance of governance in achieving sustainability. Effective boards, characterised by diversity, independence, and sustainability expertise, foster robust environmental strategies and resource allocation, thereby enhancing the financial viability of SEMPs. This study provides empirical evidence and theoretical insights into how governance structures can optimise the financial outcomes of sustainable initiatives. The findings contribute to stakeholder and legitimacy theories, showing how sustainable practices increase organisational legitimacy and stakeholder acceptance, leading to improved financial performance. From a policy perspective, the results underscore the need for guidelines and incentives to strengthen corporate governance and encourage sustainable practices in SMEs. Practical recommendations include adopting effective governance frameworks and prioritising sustainability initiatives that align with financial and environmental goals. These insights are crucial for SMEs in Ghana and other similar economies, offering a pathway to balance sustainability with profitability and long-term growth.